Lysophosphatidylcholine‐based liposome to improve oral absorption and nephroprotective effects of astaxanthin. (22nd November 2022) - Ghosh, Antara; Banik, Sujan; Suzuki, Yui; Mibe, Yasuhiko; Rikimura, Shingo; Komamoto, Tomomi; Kuromi, Koichi; Yamada, Kohei; Sato, Hideyuki; Onoue, Satomi
Abstract: BACKGROUND: The present study was aimed to develop astaxanthin (AX)‐loaded liposomes by the utilization of soybean phosphatidylcholine (PC) and lysophosphatidylcholine (LPC) to improve the nutraceutical properties of AX. AX‐loaded liposomes consisting of PC (PC/AX) and LPC (LPC/AX) were evaluated in terms of particle size distribution, morphology, release characteristics, pharmacokinetic behavior, and nephroprotective effects in a rat model of acute kidney injury. RESULTS: PC/AX and LPC/AX had uniform size distributions with a mean particle size of 254 and 148 nm, respectively. Under pH 6.8 conditions, both liposomes exhibited improved dissolution behavior of AX compared with crystalline AX (cAX). In particular, LPC/AX showed a sevenfold higher release of AX than PC/AX. After the oral administration of LPC/AX (33.2 mg AX kg −1 ) to rats, there was a significant increase in systemic exposure to AX, as evidenced by a 15‐fold higher AUC0−24 h than PC/AX. However, the oral absorption of AX in the cAX group was negligible. Based on the results of histological analysis and measurement of plasma biomarkers, LPC/AX exhibited improved nephroprotective effects of AX in the rat model of kidney injury. CONCLUSION: From these observations, a strategic application of the LPC‐based liposomal approach might be a promising option to improve the nutraceutical properties of AX. © 2022 Society of Chemical Industry.